2007
DOI: 10.1364/ol.32.002587
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear optical waveguides generated in lithium niobate by swift-ion irradiation at ultralow fluences

Abstract: A novel method to produce optical waveguides is demonstrated for lithium niobate ͑LiNbO 3 ͒. It is based on electronic excitation damage by swift ions, i.e., with energies at approximately 1 MeV/ amu or above. The new technique uses high-energy medium-mass ions, such as Cl, with electronic stopping powers above the threshold value for amorphization ͑5-6 keV/nm͒, reaching the maximum value a few micrometers inside the crystal. At the ultralow fluence regime ͑10 12 -10 13 cm −2 ͒ an effective nanostructured medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(20 citation statements)
references
References 14 publications
1
18
0
1
Order By: Relevance
“…and Er 3+ -doped telluride glass (Berneschi et al, 2007b), achieving unprecedented control over the refractive index changes of the substrate. Moreover, irradiation with swift heavy ions have been also used to produce waveguides in a wide number of materials, like LiNbO 3 (Olivares et al, 2005b(Olivares et al, , 2007bChen, 2009b;Dong et al, 2011a), KGW (García-Navarro et al, 2006), KLTN (Ilan et al, 2006), BGO , Nd:YAG (Ren et al, 2010a(Ren et al, , 2011a, Nd:GdCOB (Ren et al, 2011b), a-SiO 2 (Manzano et al, 2010), c-SiO 2 (Manzano-Santamaría et al, 2012) and chalcogenide glasses , allowing a fast fabrication of high-quality waveguides. In this section we briefly review the fabrication and properties of ion implanted waveguides in various materials, emphasizing the most recent results.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…and Er 3+ -doped telluride glass (Berneschi et al, 2007b), achieving unprecedented control over the refractive index changes of the substrate. Moreover, irradiation with swift heavy ions have been also used to produce waveguides in a wide number of materials, like LiNbO 3 (Olivares et al, 2005b(Olivares et al, , 2007bChen, 2009b;Dong et al, 2011a), KGW (García-Navarro et al, 2006), KLTN (Ilan et al, 2006), BGO , Nd:YAG (Ren et al, 2010a(Ren et al, , 2011a, Nd:GdCOB (Ren et al, 2011b), a-SiO 2 (Manzano et al, 2010), c-SiO 2 (Manzano-Santamaría et al, 2012) and chalcogenide glasses , allowing a fast fabrication of high-quality waveguides. In this section we briefly review the fabrication and properties of ion implanted waveguides in various materials, emphasizing the most recent results.…”
Section: Methodsmentioning
confidence: 99%
“…Olivares et al (Olivares et al, 2007b) also demonstrated a novel method to produce optical waveguides on lithium niobate using irradiations with high-energy medium-mass ions (i.e., swift heavy ions) at ultralow fluences (10 12 -10 13 cm -2 ). In this regime amorphous nanotracks are created by every single impact leading to an effective nanostructured medium that behaves as an optical waveguide where light propagates transversally to the ion tracks.…”
Section: Lithium Niobate (Linbo 3 or Ln)mentioning
confidence: 99%
“…Since the beginning of CMAM in 2003 photonics has been strongly developed focusing, from the fundamental point of view on the interaction with solids of high energy heavy ions, that generate material transformation by means of their high electronic excitation and therefore (electronic) damage [4,5]. From the application point of view, a novel method has been developed for the processing of optical materials based on the use of high energy ions and their electronic excitation.…”
Section: Photonicsmentioning
confidence: 99%
“…On one hand, it leads to material modification, usually, with detrimental results (as in Nuclear fusion facilities [1]) and on the other hand, it can be used to optimize or tailor the physical properties, e.g., as in waveguide fabrication [2,3].…”
Section: Introductionmentioning
confidence: 99%